Bicuspid aortic valve: evolving knowledge and new questions. Issue 1 (9th March 2022) - Sun, Byung Joo; Song, Jae-Kwan
Abstract : Bicuspid aortic valve (BAV), a common congenital anomaly with various morphological phenotypes, is also characterised by marked heterogeneity in clinical presentations including clinically silent condition with mild valvulo-aortopathy, progressive valvulopathy and complex valvulo-aortopathy with shorter life expectancy. The clinical importance of using a general and unified nosology for BAV is well-accepted by opinion leaders and an international consensus statement has been recently published, which will serve as an important scientific platform for BAV. This review describes the current knowledge of BAV based on clinical studies, addresses several unresolved issues requiring investigators' attention and highlights the necessity of prospective studies with a very long follow-up duration for better appreciation of BAV-associated valvulo-aortopathy. In addition, the progression of valvular calcification in patients with BAV and its potential contribution to development of valvulopathy will be discussed.